2010
DOI: 10.1002/ppul.21354
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high frequency percussive ventilation versus nasal continuous positive airway pressure in transient tachypnea of the newborn: A pilot randomized controlled trial (NCT00556738)

Abstract: Objective To determine whether nasal high frequency percussive ventilation (NHFPV) would decrease duration of transient tachypnea of the newborn (TTN) compared to nasal continuous positive airway pressure (NCPAP) in newborn infants. Methods A prospective, unmasked, randomized, controlled clinical trial was conducted in 46 eligible newborn infants who were hospitalized for TTN in the University Hospital of Bordeaux (France) between 2007 and 2009. Infants born by cesarian section ≥37 GA, ≥2,000g with diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 33 publications
1
33
1
2
Order By: Relevance
“…It has all the benefits of NIPPV with the added advantage of not being as dependent on breath synchronization, something that can presently be difficult to achieve with NIPPV [9]. Limited studies on the clinical use of nHFO in neonates are available, [11,12,13] and the existing data do not adequately address CO 2 elimination efficacy. All available clinical studies of nHFO have reported on blood PCO 2 comparative changes pre and post initiation of this treatment modality [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has all the benefits of NIPPV with the added advantage of not being as dependent on breath synchronization, something that can presently be difficult to achieve with NIPPV [9]. Limited studies on the clinical use of nHFO in neonates are available, [11,12,13] and the existing data do not adequately address CO 2 elimination efficacy. All available clinical studies of nHFO have reported on blood PCO 2 comparative changes pre and post initiation of this treatment modality [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Its use also does not require synchronization of breaths as the patient can comfortably continue normal tidal breathing while on the ventilator and thus has the potential to provide superior noninvasive ventilation. Only a limited number of clinical studies have explored the use of noninvasive high-frequency ventilation but whether this strategy is able to support adequate gas exchange in neonates has not been thoroughly addressed [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Dumas de la Roque et al 82 performed a prospective RCT of nasal CPAP versus nasal HFV in 40 term neonates with respiratory distress shortly after cesarean section. This was the first short-term prospective study to describe nasal HFV as an initial form of noninvasive respiratory support The gestation control fetal lambs were (1) delivered at the gestation age that the preterm lambs were delivered (FA132) or (2) delivered at the gestation age when the preterm lamb studies were completed (FA136).…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%
“…TTN is generally a benign disease and treated with a brief course of oxygen. However, some of the cases need invasive or non-invasive respiratory support 6,7,11,12 .…”
mentioning
confidence: 99%